2013
DOI: 10.3390/s130201539
|View full text |Cite
|
Sign up to set email alerts
|

Motion Mode Recognition and Step Detection Algorithms for Mobile Phone Users

Abstract: Microelectromechanical Systems (MEMS) technology is playing a key role in the design of the new generation of smartphones. Thanks to their reduced size, reduced power consumption, MEMS sensors can be embedded in above mobile devices for increasing their functionalities. However, MEMS cannot allow accurate autonomous location without external updates, e.g., from GPS signals, since their signals are degraded by various errors. When these sensors are fixed on the user's foot, the stance phases of the foot can eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
154
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(154 citation statements)
references
References 31 publications
0
154
0
Order By: Relevance
“…Activity Classification. ULISS raw data are first processed to classify the pedestrian locomotion state and the handheld device carrying mode [13][14][15]. An outcome of the classification outcome is shown in Figure 7.…”
Section: Postprocessing Pdr Algorithms With Handheld Ulissmentioning
confidence: 99%
“…Activity Classification. ULISS raw data are first processed to classify the pedestrian locomotion state and the handheld device carrying mode [13][14][15]. An outcome of the classification outcome is shown in Figure 7.…”
Section: Postprocessing Pdr Algorithms With Handheld Ulissmentioning
confidence: 99%
“…For example, [14] applies a decision tree for classification purposes while [12] uses multi-layer perceptron (MLP) and a support vector machine (SVM) to improve the performance in terms of recognition of human activity.…”
Section: B Classificationmentioning
confidence: 99%
“…The classifier introduced in [13] is based on accelerations and magnetic field data recorded with a hand-held unit. Another study dealing with different motion models and device modes is performed and reported in [14], where standing still and walking patterns are studied. An extended investigation is to add also the running mode as in [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [8], step detection and heading estimation algorithms are developed and combined with existing step length models to build a PDR system. A more advanced solution that takes different user behavior and device carrying situations into account is developed in [9]. Furthermore, simple filtering-and integration algorithms have been considered in [10] for different measurement setups.…”
Section: Introductionmentioning
confidence: 99%